Violation of the rules of sport and liability of athletes for damage - Miodrag Mićović (Zbornik Radova Pravnog Fakulteta u Splitu, 2015)
The breach of sport rules by athletes may be the outcome of many sports activities. Thus, it is not uncommon that as a result of violation of sport rules arise damage for one of the participants in sports activities. With respect of that, question arises whether the injured party is entitled to request compensation for damages, and if so, which rules would be applicable for determining liability of the party who caused a damage? A possible solution to this issue is contained in the Law on Sport of the Republic of Serbia. Along with legal analysis of the respective solution, the article presents theoretical views on the criteria that should be taken into account when determining liability, as well as the possible basis for exclusion of liability of athletes.